Cave dogs around major urban areas of Arequipa, Peru, threaten rabies elimination program - Castillo-Neyra, Ricardo; Díaz, Elvis W.; Bellotti, Brinkley Raynor; Morucci, Katherine; De la Puente-León, Micaela; Ortiz-Cam, Lizzie; Levy, Michael Z. (Frontiers in Veterinary Science, 2025)
BackgroundIn the city of Arequipa, Peru, the government has implemented control measures against dog rabies virus since the detection of its reintroduction in 2015. The city was previously considered free of animal reservoirs, except for free-roaming owned dogs, animals with identifiable owners but allowed to move unsupervised, and stray dogs, which include both abandoned and street-born dogs that roam freely while relying on human settlements for food, within its urban boundaries. However, multiple reports from peri-urban residents have suggested the presence of feral dogs, a population living independently of humans on the city's outskirts. We aim to document the presence and dietary patterns of feral dogs adjacent to the city margins.MethodsWe conducted monthly field visits to four peri-urban localities in eastern Arequipa, an area where the presence of feral dogs had been previously reported. Dog caves were identified by tracking footprints and other field signs left by dogs, and their locations were georeferenced. Each cave was revisited monthly three times to record the presence of live and dead dogs, and puppies. Fecal samples collected around the caves were analyzed to assess dietary patterns.ResultsWe observed that feral dogs use caves for resting, hiding, and reproduction—some of which appear to be constructed by the dogs themselves. The high number of puppies and dead adult dogs indicates a high population turnover. Dietary analysis revealed that these dogs feed on local fauna, including birds, rodents, cats, sheep, and, notably, other dogs.ConclusionsThese unowned, cave-dwelling dogs are not reached by mass rabies vaccination or sterilization programs. Moreover, they exist outside the jurisdiction of health inspectors responsible for rabies surveillance, resulting in a lack of data on rabies infection in this subpopulation. Our findings highlight the need for integrated One Health strategies to address the potential challenges posed by feral dog populations in rabies elimination efforts.